ANALISIS PENGARUH BRAND AWARENESS, BRAND IMAGE, BRAND TRUST TERHADAP BRAND LOYALTY MINUTE MAID PULPY ORANGE DI KOTA PADANG - Rahmawati Rahmawati; Ma'ruf Ma'ruf (Politeknik Negeri Lhokseumawe, 2020)
This study aims to obtain empirical evidence on the influence of brand awareness, brand image and brand trust on the loyalty to a ready to drink (RTD) fruit beverage product in the city of Padang. Based on quantitative approach, data collected with questionnaire and respondents were selected with purposive sampling technique. The number of filled questionnaire was 293 from 350 distributed. Hypothesis testing is done by using Structural Equation Modeling (SEM) using AMOS version 24 software program . Statistical analysis reveals that brand awareness has a significant influence on brand image but has no significant effect on brand trust and brand loyalty. This Study also obtained the results that the brand image has a significant and positive impact on brand trust, but surprisingly brand image does not have a significant effect on brand loyalty. And form this study we found Brand trusts have a positive and significant influence on brand loyalty. This study provides insights that in RTD beverage industry in Padang city, awareness about the brand is not enough to obtain loyalty to particular brand. Thus, marketers should find an appropriate program in their communications to the customers. Some limitations and future research are discussed.Keywords: Brand Awareness, Brand Image, Brand Trust, Brand Loyalty, RTD fruit beverage industry